Edukasi dan Pemeriksaan Fisik Kesehatan Telinga pada Pekerja Usia Produktif - Sukmawati Tansil Tan; Fernando Nathaniel; Yohanes Firmansyah (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Educational activities and physical examinations regarding ear canal hygiene and tympanic membrane health have the aim of increasing public knowledge about the importance of maintaining ear hygiene and maintaining the integrity of the tympanic membrane. In this activity, counseling is given to the public to provide a correct understanding of cerumen, proper ear care, and signs of damage to the tympanic membrane. This community service activity was carried out on June 9, 2023 by involving 52 respondents. All respondents attended community counseling and physical examinations. On the results of the physical examination it was found that 3 (5.8%) respondents had a perforated tympanic membrane, and 6 (11.5%) respondents had prop cerumen. The results of this educational activity and physical examination are expected to increase public understanding of the importance of maintaining ear hygiene and maintaining the health of the tympanic membrane. With the right knowledge, it is hoped that people will be able to adopt healthy habits in caring for their own ears and take the necessary precautions to maintain optimal ear health.